Identifying Popular Indigenous Leafy Vegetables for Sustainable Interest in Vegetable Production in the Tamale Metropolis in the Northern Region of Ghana - Yakubu, Fuseini Jacob; Kumah, Patrick (International Journal of Environment, Agriculture and Biotechnology, 2019)
One way of achieving a sustained interest in vegetable production in a catchment area is to identify the most popular vegetable with high demand. The present study determined the Popular Indigenous leafy vegetables in the Tamale Metropolis in the Northern region of Ghana. A structured questionnaire was used to access the requisite data. The items were divided into sections. Most of the items were close-ended questions with few open-ended ones to make room for more different opinions. The questionnaire covered the bio data of leafy vegetable marketers and consumers, buying and selling volumes of leafy vegetables, Leafy vegetable marketers and prospective leafy vegetable consumers were the target population. The population of 60 marketers of leafy vegetables and 274 consumers in the Tamale Metropolis were considered. Respondents (consumers) were chosen as they came to buy leafy vegetables at the market. The data obtained was subjected to one way analysis of variance (ANOVA), using Statistical Package for Social Sciences (SPSS Version 16.0). Amaranthus dubius, Corchorus olitorius, and Hibiscus sabdariffa were rated the most popular leafy vegetables.